An Evaluation of Change Management at British Airways: A Case Study - Khicha, Nidhi (2008)
Organizational change and innovation are essential for a company's growth and development. Having understood the importance of managing organizational change and innovation, many researchers have formulated theories related to change management. These theories have been critically analyzed in this paper along with an example of British Airways. The innumerable changes taking place at British Airways give a deeper understanding of change is implemented in organizations. This paper confirms the findings of other researchers that it is difficult to implement change unless there exists mutual trust and obligation between the employer and employee.